Distributed Spaceborne SAR: a review of systems, applications, and the road ahead - Hu, Cheng; Li, Yuanhao; Chen, Zhiyang; Liu, Feifeng; Zhang, Qingjun; Monti-Guarnieri, Andrea V.; Hobbs, Stephen E.; Anghel, Andrei; Datcu, Mihai (Institute of Electrical and Electronics Engineers (IEEE), 2025)
As a crucial sensor for wide-area Earth observation, spaceborne synthetic aperture radar (SAR) plays a pivotal role in large-scale terrain mapping, ocean observation, disaster monitoring, and so forth. Driven by the increasing demands for diverse applications, enhanced performance, and the continuous advancement of satellite and radar technologies, the distributed configuration has emerged as a key developmental trend for spaceborne SAR. This review comprehensively summarizes the systems and typical applications of distributed spaceborne SAR. The system configurations encompass homogenous distributed SAR, formed by multiple identical or similar platforms, and heterogeneous distributed SAR, characterized by significant differences between the transmitting and receiving platforms. Typical applications of distributed SAR include intelligent target recognition, terrain mapping, deformation retrieval, atmosphere measurement, and ocean observation, among others. Finally, the review offers a prospective outlook on the future development of distributed spaceborne SAR.
Keywords: Spaceborne radar; Satellites; Synthetic aperture radar; Orbits; Terrain mapping; Imaging; Sea measurements; Reviews; Extraterrestrial measurements; Atmospheric measurements; 37 Earth Sciences; 40 Engineering; 3704 Geoinformatics; 4013 Geomatic engineering; 4603 Computer vision and multimedia computation